Deleuze and sex - Beckman, Frida (Deleuze connections., 2011)
Applies Deleuze's philosophical ideas, such as the body-machine and becoming, to sex. These 12 new essays develop a fresh philosophical approach to the study of sex and sexuality as practice. The contributors pursue the restricting as well as the liberating force of sex in relation to a spread of themes and subjects including the limits of the human, bacteria, death, disability and animality.